2022
DOI: 10.14740/jmc4013
|View full text |Cite
|
Sign up to set email alerts
|

Remimazolam for Sedation During Upper Gastrointestinal Endoscopy in an Adolescent

Abstract: Remimazolam is a short-acting benzodiazepine that has recently received approval from the US Food and Drug Administration (FDA) for procedural sedation in adults. Similar to other benzodiazepines such as midazolam, remimazolam has sedative, anxiolytic, and amnestic properties. Rapid metabolism by plasma esterases results in a half-life of 5 -10 min and a limited context sensitive half-life. Preliminary data from adult studies have demonstrated favorable hemodynamic stability, no pain on injection, and limited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 17 publications
2
2
0
Order By: Relevance
“…33 A study of a 15-year-old child with multiple drug and food allergies who underwent oesophagogastroduodenoscopy showed that low-dose of remimazolam besylate (initial dose 0.03 mg/kg; maintenance dose 20µg/kg/min) was equally safe under spontaneous ventilation and a natural airway. 34 In addition, remimazolam significantly reduced the incidence of injection pain based on the phenol structure and improved the comfort of children undergoing gastroscopy, consistent with previous studies. 35…”
Section: Current Status Of Applications Of Remimazolamsupporting
confidence: 87%
“…33 A study of a 15-year-old child with multiple drug and food allergies who underwent oesophagogastroduodenoscopy showed that low-dose of remimazolam besylate (initial dose 0.03 mg/kg; maintenance dose 20µg/kg/min) was equally safe under spontaneous ventilation and a natural airway. 34 In addition, remimazolam significantly reduced the incidence of injection pain based on the phenol structure and improved the comfort of children undergoing gastroscopy, consistent with previous studies. 35…”
Section: Current Status Of Applications Of Remimazolamsupporting
confidence: 87%
“…When used as the primary agent for the induction of general anesthesia, doses up to 0.2 mg/kg have been reported. Infusions, titrated to effect, have varied from 1 - 2 mg/kg/h, which is similar to our dosing range of 15 µg/kg/min and that reported anecdotally in pediatric patients [ 16 - 18 ]. Given its rapid onset, the clinical effect of sedation can generally be achieved within 10 - 15 minutes of starting the infusion without a bolus dose.…”
Section: Discussionsupporting
confidence: 72%
“…To date, published experience with the use of remimazolam in pediatric-aged patients remains anecdotal, primarily from individual case reports and small case series [16][17][18]. Dosing in both adults and children has included bolus administration and continuous administration.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its use as the primary agent for procedural sedation, remimazolam has been shown to be an effective primary agent or adjunct to general anesthesia in adults [17][18][19]. To date, reports regarding the use of remimazolam in pediatric-aged patients have included only anecdotal retrospective experiences from single case reports or small case series [20][21][22][23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%